Influence of clay minerals on oxidation reaction of light crude oil. (4th March 2019) - Guowei, Qin; Yaling, Wang; Xu, Dai; Wenlong, Qin; Mei, Wu; Yanzhao, Zheng
Abstract: By means of the static oxidation test of crude oil, the influence of clay minerals on the light crude oil oxidation reaction under reservoir temperature and pressure was investigated by means of orthogonality analysis method. Based on the thermogravimetric analysis, the oxidation characteristics of clay minerals on crude oil during heating were analyzed. The results show that the clay minerals have different catalytic effects on light crude oil, of which montmorillonite has the best catalytic effect and kaolinite has the worst. And they have the positive effect to light crude oil on air injection, which could enhance oil recovery.